ANALYSIS OF SCHOOL PRINCIPALS' LEADERSHIP STYLE IN INCREASING TEACHER MOTIVATION IN 15 STATE PRIMARY SCHOOLS (SDN) BONE BOLANGO DISTRICT, GORONTALO PROVINCE - Ibrahim, Sri Susanti; Rachman, Ayu Anastasy; Napu, Karlina (Jurnal Ilmu Manajemen dan Bisnis, 2024)
The aim of this research is1) to find the leadership style of the principal at State Elementary School (SDN) 15 Kabila, Bone Bolango Regency, Gorontalo Province. 2) Analyze the leadership style of the principal in increasing teacher motivationat State Elementary School (SDN) 15 Kabila, Bone Bolango Regency, Gorontalo Province. The method in this research uses a qualitative case study method with data collection techniques of observation, interviews and documentation.There were 5 interview informants consisting of school principals and teachers.The research results show that 1) The leadership sty lecreated by the principal at State Elementary School (SDN) 15 Kabila, Bone Bolango Regency, Gorontalo Provinceuses a democratic leadership style demonstrated by the principal and his subordinates, providing an example of good cooperation by organizing, directing and guiding the staff. Education so that they work together 2) The principal's leadership style in increasing motivationis good. This can be seen from the leadership style which creates togetherness between students and leaders, the principal holds training, seminars and other training because there are activities to improve the quality of the leader, as well as teacher memorabilia. Apart from that, if the teacher has good performance, the principal provides rewards in order to increase motivation. The principal always tries to maintain a conducive worken vironment.